2018
DOI: 10.1109/tbc.2017.2704425
|View full text |Cite
|
Sign up to set email alerts
|

Low Latency Parallel Turbo Decoding Implementation for Future Terrestrial Broadcasting Systems

Abstract: Xun. (2017) Low latency parallel turbo decoding implementation for future terrestrial broadcasting systems. IEEE Transactions on Broadcasting. pp. 1-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, the forward and backward recursions impose data dependencies, which limit the achievable degree of parallel processing, resulting in high processing latency. Several approaches have been proposed to improve the throughput and latency of the Log-BCJR turbo decoder, most of which focus on increasing the parallelism of the conventional turbo decoder [33,[38][39][40]. To be more specific, we have previously proposed a FPTD algorithm [33,41], which dramatically increases the parallelism of the decoding process and achieves significantly lower latency, by dispensing with the recursions of the Log-BCJR algorithm.…”
Section: B Fully-parallel Turbo Decodermentioning
confidence: 99%
“…However, the forward and backward recursions impose data dependencies, which limit the achievable degree of parallel processing, resulting in high processing latency. Several approaches have been proposed to improve the throughput and latency of the Log-BCJR turbo decoder, most of which focus on increasing the parallelism of the conventional turbo decoder [33,[38][39][40]. To be more specific, we have previously proposed a FPTD algorithm [33,41], which dramatically increases the parallelism of the decoding process and achieves significantly lower latency, by dispensing with the recursions of the Log-BCJR algorithm.…”
Section: B Fully-parallel Turbo Decodermentioning
confidence: 99%
“…This will enable the user to design complex hardware designs [10]. The researchers in [1] using parallelism level 64 for frame size 2048-6144 and parallelism level 8 for frame size 256-2048 and using an interleaver proposed by them, and they conclude that the result of performance and latency that could use turbo code in future terrestrial broadcasting (TB) systems. And in research [2] a comparison between turbo code, LDPC, polar code was done the result showed that the turbo code made the best performance than the others in error correction and flexibility in using different block sizes and different code rates.…”
Section: Fig 1 General Block Diagram Of Digital Communication Systemsmentioning
confidence: 99%
“…Baseband signal processing such as channel estimation, channel equalization, channel encoding, etc, are the important parts of wireless communication systems to resist fading channel [8][9][10][11], where channel estimation is especially critical for massive MIMO systems. In massive MIMO systems, accurate and efficient channel estimation is a challenging problem and an open research issue, because the number of channel parameters to be estimated is very large as the antennas increase, while the number of pilots adopted by channel estimation is limited to make sure a high spectrum efficiency.…”
Section: Introductionmentioning
confidence: 99%